Influence of Pre-Aging on the Artificial Aging Behavior of a 6056 Aluminum Alloy after Conventional Extrusion - Lisa Winter; Kristin Hockauf; Mario Scholze; Ralph Jörg Hellmig; Thomas Lampke (Metals, 2021)
In the present study, the influence of the initial heat-treatment conditions on the artificial aging behavior after conventional linear extrusion at room temperature was investigated for the precipitation hardening of a 6056 aluminum alloy. A solution-annealed condition was systematically compared to naturally-aged and pre-aged conditions. Differential scanning calorimetry was used for analyzing the precipitation sequence and its dependence on the initial heat treatment. The natural aging behavior prior to extrusion and the artificial aging behavior after extrusion were determined by microhardness measurements as a function of the aging time. Furthermore, the microstructure, dependent on the induced strain, was investigated using optical microscopy and transmission electron microscopy. As a result of pre-aging, following a solid-solution treatment, the formation of stable room-temperature clusters was suppressed and natural aging was inhibited. The artificial aging response after extrusion was significantly enhanced by pre-aging, and the achieved hardness and strength were significantly higher when compared with the equally processed solution-annealed or naturally-aged conditions.